Georgia Architectural and Historic Properties Survey of Quitman [270] Old Madison Road, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Quitman [270] Old Madison Road, Valdosta, Ga. December 1980. Large two story rectangular plan house. Hipped tile roof. Hipped dormer. Brackets. Surrounding shed porch with round posts and brick piers. Interior and exterior chimneys. Transom and sidelights. Port cochere at left. Second story bay at facade. Two story central portico. Semi-circular drive leads up to house. Excellent condition. Date of Construction: c. 1920. At the entrance are two stone grist wheels. It is possible that the owners are in the milling business. Architecturally, a fine country house. It does not follow a particular style, but has many architectural elements that work well together, forming a nice effect.
Georgia Architectural and Historic Properties Survey of Quitman [270] Old Madison Road, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.25 MB (1,311,714 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)